URBAN SOLID WASTE MANAGEMENT FROM SOURCE TO DESTINATION (CASE STUDY: ASTARA CITY) - Ramin Haji Amiri, Alireza Poursheykhian, Hossein Asghari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Municipal waste management is a complex and multifaceted process that requires the serious determination of the responsible agencies and the cooperation of other sectors that are directly and indirectly involved in this matter. Astara is one of the northernmost cities of Iran and the westernmost city of Gilan province and with its unique environmental features, it needs a regular planning for waste management; Because it is adjacent to both the sea and the forest, and this factor, if not properly managed, will cause the fragility of these two environmental factors. In this research, using descriptive-analytical method, while analyzing the current situation of waste management in Astara city, using SWOT analytical model, the strengths and weaknesses, opportunities and threats of waste management in the city have been investigated; In this way, field methods, observation, questionnaires and interviews with experts have been used. The results of the research show that the weaknesses of waste management in the city of Astara outweigh the strengths and the opportunities against threats have not been used properly. Therefore, by identifying the strengths and weaknesses and opportunities and threats of waste management in the city of Astara, it is possible to overcome the existing problems and plan and plan waste management in the future horizons.